Contemporary management of prostatic abscess: Our experience - Amrendra Pathak; Manish Kiran Shrestha; Sudhir Khanna; Juhil Dipak Nanavati; Om Prakash Prasad; Arun Gupta; Tejas Mistry (Urology Annals, 2022)
Introduction: Prostatic abscess is a serious urological problem that needs immediate attention due to its high morbidity and mortality in absence of appropriate treatment. The objective of our study is to evaluate the efficacy and safety of various modalities of management of prostatic abscess: medical management (MM), transrectal ultrasound-guided aspiration (TRUS-GA), and transurethral deroofing (TU-DR). Methods: This retrospective study was done in a tertiary care center after taking approval from the institutional review board. Conservative management was done by oral or parenteral medications. Transrectal ultrasound GAs were performed under local anesthesia with an 18-gauge two-part needle. Collapse of cavity was seen in “real time” on TRUS. TU-DR of the prostate was done by 26 French continuous irrigation monopolar resectoscopes. The aspirated pus was sent for microbiological investigation. Results: TRUS-guided aspiration was performed in 20 patients, TU-DR in five patients, and conservative management in 15 patients. The mean volume of abscess aspirated by TRUS guidance was 13 cc (range 8–50 cc) with single-time aspiration in 85% of cases. Re-aspiration was done in 3 patients. The mean volume of abscess was 33.2 cc (range: 25–40 cc) in TU-DR group and 1.2 cc (range 0.5–2.0 cc) in the MM group. The predominant organism isolated was Escherichia coli (48%). Clinical improvement was seen in 97.5% of cases. Conclusion: We suggest TRUS-GA for symptomatic patients with abscess size more than 2 cc and TU-DR if TRUS-GA fails or is contraindicated.